The Alternative Strategy For Strengthening Indonesian Textile and Clothing Industry Structure - ALLA ASMARA; YETI L. PURNAMADEWI; SRI MULATSIH; TANTI NOVIANTI (Jurnal Bisnis Manajemen, 2016)
Indonesian textile and clothing industry (TPT) is an industry most affected by markets dynamics growing (domestic and international). Strengthen the industrial sector is important aspects to guarantee the existence of Indonesian TPT industry. The purposes of this study are: (1) analyze the internal factors (strengths and weaknesses) of Indonesian TPT industry, (2) analyze the external factors (opportunities and threats) of Indonesian TPT industry, (3) formulate the alternative strategies to strengthen the Indonesian TPT industry, and (4) formulate the priority strategies to strengthenthe Indonesian TPT industry structure. SWOT and QSPM method used to answer the research objectives. The study results indicate that raw material is key factor for strengthening Indonesian TPT industry structure. Other key factors are human resource, infrastructure, market/marketing, product, production process, strategy/policy, and financial. On the internal side, the main strength is a variety of raw material alternative sources, while the main weakness is not always able to guarantee the raw material quantity, quality, and continuity. On the external side, international market product price tends to increase considered as major opportunity. Meanwhile, the main threat is in the high level of competition in domestic/international market. According to internal and external conditions, the position of Indonesian TPT industry in SWOT quadrant is in quadrant II, has strength but facing threat.